Netherton Syndrome: A Case Report With Literature Review - Fereshteh Salari; Leila Bani Adam; Saba Arshi; Mohammad Hassan Bemanian; Morteza Fallahpour; Mohammad Nabavi (Mazandaran University of Medical Sciences, 2019)
Introduction: Netherton Syndrome (NS) is a rare hereditary autosomal recessive disorder with ichthyosiform cutaneous lesions, specific hair shaft defect, and atopic diathesis. The incidence of NS is estimated to be approximately 1 in 200000. The objective of this case report is to present NS in a patient with severe eczema atopic dermatitis-like eruption. Case Presentation: A 41-month-old boy was referred to the clinic of Allergy and Immunology, Hazrat Rasoul Hospital with generalized erythema, and scaling cutaneous lesions. The patient underwent clinical examinations and laboratory analysis. His laboratory data revealed only an elevated IgE level with a leukocyte count of 7800/μL containing 10% eosinophil. His hair shaft indicated classic trichorrhexis invaginata (Bamboo hair). Based on the clinical and laboratory findings, he was diagnosed with NS. A brief review was also done related to this case. Conclusion: This case was reported because of the severity of the disorder and other differential diagnoses in severe and refractory atopic dermatitis-like eruptions. The importance of the case is related to other differential diagnoses, especially with early onset disorders at neonatal age. Log in to use Ginger Limited mode ichthyosiform ×